TRANSPLANTING COMMON LAW PRECEDENTS: AN APPROPRIATE SOLUTION FOR DEFECTS OF LEGISLATION IN VIETNAM, (part 2) - Do, Thi Mai Hanh (European Scientific Journal, ESJ, 2014)
Vietnam is in the midst of legal and judicial reforms as it attempts to construct an appropriate framework for a successful market-based economy. It is increasingly likely that as its legal system has been changed to complement a market economy, an added degree of unpredictability has entered the situation, particularly due to the degree of legal transplantation involved. Vietnam has imported legal rules from the Civil Law and the Common Law, altering its legal system and blurring previously clear structural lines. Further change can be anticipated, and with due consideration, welcomed. Recently, the Vietnamese government has been planning to borrow Common Law precedents as a solution to fill the gaps in its sources of law, which have traditionally been of legislative origin. These sources include Codes, Laws, Ordinances, Decrees, Resolutions, and Circulars. Precedents and customary laws, on the other hand, have not been officially recognized. Partly due to the acceptance of a single source of law i.e. legislation, the application of law in Vietnam is critically evaluated not to be consistent, uniform and effective. Further, a lack of adequate legal interpretation, the uncertainty and the deficiency of the legislation constitute shortcomings of the legal system. Precedents are major sources of law in the Common Law system which is one of the most pre-eminent legal families in the world. As sources of law, precedents are usually considered to possess merits that make the legal system certain, consistent, fair, predictable and stable. Therefore, with those strengths, precedents can supply the certainty and stability which legislation lacks. Several factors favour the integration of precedents. Beside the need for Vietnam to counter the weakness of its legislation and the apparent strengths offered by precedents to fill legislative gaps are the readiness of Vietnam for judicial reform and the strong possibility of success of legal transplants whose success has elsewhere generally been confirmed. These provide strong motives for Vietnam to transplant precedents into its legal system. Therefore, the introduction of the Common Law precedents is completely an appropriate solution for defects of the Vietnamese legislation.